Infrared thermal imaging for assessing human perspiration and evaluating antiperspirant product efficacy - Hrebesh Molly Subhash; Tochukwu Ofoegbuna; Abmael H. Oliveira; Mark C. Pierce; Shyamala Pillai (Scientific Reports, 2024)
Abstract In humans, perspiration regulates core body temperature. Therefore, objectively evaluating it is essential for studying sweat gland function and mechanisms, particularly in antiperspirant efficacy studies. Various approaches have been developed for measuring human perspiration and evaluating antiperspirant efficacy, but are unsuitable for robust and routine clinical testing applications. This paper shows how infrared thermography, utilizing both high- and low-resolution modes, functions as a multiscale imaging modality. The high-resolution mode extracts physiological parameters (respiratory ~ 0.3 Hz and heart rate ~ 1.0 Hz) and visualizes the reduction of the sweat pore radii (from 359 ± 155 μm to 161 ± 47 μm) after antiperspirant application, consistent with known mechanisms of pore plugging and constriction induced by aluminum salts. The low-resolution mode quantitatively maps sweat retention in underarm clothing. All study participants in a clinical trial showed reduced sweat retention on their T-shirts due to antiperspirants, with reductions ranging from approximately 37–97% and an average reduction of 77.7 ± 22.1% using the developed methodology and tested antiperspirant. Overall, this non-invasive technique presents significant potential for clinical and personal care product evaluations, particularly in the early stages of product development.